THE TRANSFORMATION STRATEGY AND SAFETY IMPLEMENTATION OF CULTURE CHANGE AT PT PERTAMINA DRILLING SERVICES INDONESIA - Muhammad Arifin; Chaerudin Chaerudin (Dinasti International Journal of Education Management And Social Science, 2020)
This research had purposed to analyzed those Transformation Strategy and Safety Implementation of Culture Change in improving the Occupational Safety and Health from PT Pertamina Drilling Services Indonesia during period 2015-2020. These research data was result from in-dehpt, interview, FGD, primary and secondary data from PT Pertamina Drilling Services Indonesia during these implementation of HSE Work culture change program during period of 2015-2020. Research method used qualitative with type of case study research. Data analysis used Mckensy 7S Framework and The results showed that PT Pertamina Drilling Services Indonesia has a strategic plan for any kind of transformation from HSE Work culture until 2030 through "Salam Lima Jari" program. Through planned and systematic program until 2020, PT Pertamina Drilling Services Indonesia has succeeded in putting HSE Work culture at Proactive level. The ability of PT Pertamina Drilling Serrvices Indonesia to create strategic planning and implement HSE programs should be encouraged by ability to strengthen system and program integration within organization. The Succeed of HSE culture will achieved if there has supported by consistent commitment from management and all related units in established HSE culture as the main lifestyle at organization therefore HSE culture did not stop at cognitive and psychomotor aspects of employees but also its holistically becomes an effective organization.